(untitled) (Research, Society and Development, 2020)
The genus Salmonella spp. It belongs to the Enterobacteriaceae family and are bacteria that have a worldwide distribution, being present, especially, in animal production environments. About 1.9% of the cases of foodborne diseases caused by Salmonella are transmitted by pork meat and its derivatives, according to data from the Ministry of Health. In view of the above, this article aimed to investigate Salmonella in swine animals from growing meat trade and concern for public health. This study is an integrative review, covering scientific articles, monographs, theses and dissertations published in the databases: CAPES, SciELO and Google Scholar. Through studies, it is found that Salmonella spp. It is one of the main agents involved in foodborne diseases and pigs are considered important vehicles of these bacteria, acting as a source of infection, directly or indirectly, to humans. Finally, it can be concluded that the main objective of the study can be achieved, emphasizing the importance of reporting the cases of Salmonella contamination to the control departments, in order to direct the sanitary hygienic control measures, in order to ensure the safety of food of porcine origin and its derivatives, and the health of consumers.